The relationship between children's perceptions of the natural environment and their subjective well-being. Issue 6 (1st November 2016) - Adams, Sabirah; Savahl, Shazly; Casas, Ferran
Abstract : The overarching aim of the study was to ascertain the relationship between children's perceptions of the natural environment and their subjective well-being. More specifically the study aimed to fit a structural model depicting the nature of the relationship between children's environmental views and their global, and domain-specific life satisfaction. The sample included 1004 twelve-year-old participants randomly selected from 15 primary schools in Cape Town, South Africa. The measuring instrument included the New Ecological Paradigm (NEP) Scale for children, the Students' Life Satisfaction Scale and the Personal Well-Being Index-School Children. Confirmatory factor analysis was used to test the validity of the NEP Scale which showed appropriate fit structure. A good fit structure was also found for the overall structural equation model. However, the overall model showed that children's environmental views were not related to their global life and domain-specific life satisfaction. At a foundational level, more research is required to allow for a better understanding of how children in differing circumstances construct and assign meaning to nature, and what their perceptions of nature are before we can begin to ask them when, how or why they engage in nature.